Qualitative Empirical Analysis of IT Talent Provider Customer Satisfaction in Indonesia - Ravindra Safitra Hidayat; Panca Maulana; Eryco Muhdaliha (Green Economics: International Journal of Islamic and Economic Education, 2025)
This study explores the factors influencing customer satisfaction in Indonesia's IT talent provider industry through a qualitative empirical analysis. Employing secondary data sources such as academic literature, industry reports, and customer feedback, the research identifies key drivers of satisfaction, including project-based work setups, client involvement, teamwork dynamics, the nature of work, and employee engagement. Findings suggest that customer satisfaction is a multifaceted concept influenced by effective communication, cohesive teamwork, and robust talent management strategies. The study underscores the need for IT talent providers to adopt comprehensive approaches to enhance service quality, retain skilled professionals, and meet evolving client demands, thereby strengthening their competitive position.